2020
DOI: 10.33263/briac111.82338241
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Nanotechnology in the Fight Against COVID-19

Abstract: Coronavirus disease (COVID-19) is a respiratory infectious disease caused by a newly discovered virus strain, severe acute respiratory syndrome coronavirus-2 (SARS-Cov-2). This pandemic spread quickly across nations with a high mortality rate in immunocompromised patients. This contagious disease posed a serious threat to health systems. It impacted the continents of the earth in a way that could not have been predicted. Therefore, many leading funding agencies announced the call for proposal to diagnosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Wang et al, demonstrated the potential of Se coatings on polycarbonate medicinal tools where Se coating remarkably inhibited S. aureus growth to 27% after 72 h in comparison with an uncoated polycarbonate surface [ 178 ]. The antimicrobial properties of SeNPs can be effectively harnessed by using disinfectants supplemented with these unique NPs which can be used for effective prevention of this highly contagious viral infection [ 179 , 180 ]. Altogether, these finding demonstrates that SeNPs could be considered as a novel, promising therapeutic strategy against the COVID-19 pandemic and other infections [ 41 , 181 , 182 ].…”
Section: Senps As a Rational Approach Against Viral And Bacterial Inf...mentioning
confidence: 99%
“…Wang et al, demonstrated the potential of Se coatings on polycarbonate medicinal tools where Se coating remarkably inhibited S. aureus growth to 27% after 72 h in comparison with an uncoated polycarbonate surface [ 178 ]. The antimicrobial properties of SeNPs can be effectively harnessed by using disinfectants supplemented with these unique NPs which can be used for effective prevention of this highly contagious viral infection [ 179 , 180 ]. Altogether, these finding demonstrates that SeNPs could be considered as a novel, promising therapeutic strategy against the COVID-19 pandemic and other infections [ 41 , 181 , 182 ].…”
Section: Senps As a Rational Approach Against Viral And Bacterial Inf...mentioning
confidence: 99%
“…Low-cost antibody-linked graphene sheets that function as environmental virus sensors have been synthesized; their application as coatings on face masks/PPEs represents a promising strategy to fight COVID-19 by minimizing the risk of transmission (Palmieri and Papi 2020). Moreover, magnetic nanomaterials or nanoparticles can be exploited as efficient alternatives for coating PPEs such as masks and eyeprotecting glasses in order to produce reusable and environmentally friendly antiviral nanocoated PPEs (Tyagi et al 2021). However, antiviral nanoparticles such as silver (Ag), copper (Cu), copper oxide (CuO), and zinc (Zn) have been incorporated on surfaces and PPE textiles, and can be a viable alternative to chemical disinfection processes (Valdez-Salas et al 2021;Ruiz-Hitzky et al 2020).…”
Section: Disinfection and Its Deleterious Effects On Humans And The Environmentmentioning
confidence: 99%
“…Metal nanoparticles showed broad-spectrum antimicrobial activities [ 90 , 91 ]. Incorporating nanoparticles or plant extracts into the tiles increases the reduction potential against microorganisms [ 92 94 ].…”
Section: Current Scenario and Future Perspectivementioning
confidence: 99%